2012
DOI: 10.1088/0741-3335/54/8/085023
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of complex patterns observed in the electron-cyclotron instability of a mirror confined plasma produced by an ECR discharge

Abstract: A specific nonlinear regime of electron-cyclotron instability is discussed aimed at explaining the complex temporal patterns of stimulated electromagnetic radiation from a mirror trap with a non-equilibrium plasma typical of an ECR discharge. This regime is characterized by self-modulation of a plasma cyclotron maser due to coherent interference of two counter-propagating unstable waves with degenerate frequencies resulting in the spatial modulation of the amplification coefficient. The proposed simple theoret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…1, maximum detuning ω ce /ω ≈ 1.32 is observed at the initial phase of the instability development just after the first broadband pulse. This indicates that Used model is discussed in [38,41]; modeling is performed for the following initial conditions relevant to the experimental shot shown in fig. 1:…”
mentioning
confidence: 99%
“…1, maximum detuning ω ce /ω ≈ 1.32 is observed at the initial phase of the instability development just after the first broadband pulse. This indicates that Used model is discussed in [38,41]; modeling is performed for the following initial conditions relevant to the experimental shot shown in fig. 1:…”
mentioning
confidence: 99%
“…In all cases, the cyclotron-maser instability is presumed to be driven by an electron horseshoe or modified horseshoe-ring distribution. Scaled laboratory experiments have demonstrated the potential for such horseshoe distributions to generate narrowband cyclotron-maser emission at GHz frequencies over distances of a few meters [21][22][23][24][25].Although the generation mechanism is well established, there remain important questions with regard to how the radiation may propagate within the parent auroral density cavity and ultimately escape [26]. Cairns et al [27] have demonstrated how the radiation, generated just below the electron cyclotron frequency, may successfully couple onto the upper branch of the plasma dispersion relation and escape.…”
mentioning
confidence: 99%
“…In all cases, the cyclotron-maser instability is presumed to be driven by an electron horseshoe or modified horseshoe-ring distribution. Scaled laboratory experiments have demonstrated the potential for such horseshoe distributions to generate narrowband cyclotron-maser emission at GHz frequencies over distances of a few meters [21][22][23][24][25].…”
mentioning
confidence: 99%
“…The instability is triggered by the stored electron energy accumulated 16 into the anisotropic EED with v ? ) v k (with respect to the confining magnetic field) and a (local) positive slope of the EED, i.e., df ðEÞ dE > 0.…”
Section: Introductionmentioning
confidence: 99%